PENGARUH PEMBERIAN VITAMIN C DAN E TERHADAP GAMBARAN HISTOLOGIS TESTIS MENCIT (Mus musculus L.) YANG DIPAJANKAN MONOSODIUM GLUTAMAT (MSG) - Ummi Kalsum; Syafruddin Ilyas; Salomo Hutahaean (Saintia Biologi, 2013)
The aim of this study is to determine the effect of vitamin C and E on testicular histology of mice following exposure to monosodium glutamate (MSG) for 30 days. Completely Randomized Design (CRD) consisting of 6 treatments and 5 replications was used in this experiment. Mice were treated daily by oral gavage with 4 mg MSG (P1), 4 mg MSG + 0,26 mg vitamin C (P2), 4 mg MSG + 0,026 vitamin E (P3), and 4 mg MSG + 0,26 mg vitamin C + 0,026 mg vitamin E (P4). All dosages (mg/g) were given based on body weight. Two control groups K- and K+ treated with water and castor oil respectively. The results showed that MSG decrease testis weight and its volume (P<0,05), MSG also decrease the diameter of seminiferous tubule and the number of spermatogenic cells. Vitamin C recovers testis weight (P<0,05), but cannot recover its volume, diameter of seminiferous tubules and the number spermatogenic cells (P>0,05). Vitamin E increases the weight and volume of the testes and spermatogenic cells (P<0,05), but unable to recover diameter of the seminiferous tubules (P>0,05). The combination of vitamin C and E recover testis weight and its volume, seminiferous tubule diameter and number of spermatogenic cells (P<0,05). Keywords: Monosodium Glutamate, Vitamin C, Vitamin E, Testis